Variation of the number of flowering stems and its effect on forage yield in a population of Phalaris aquatica L. in Greece - Dini-Papanastasi O.; Goulas C.K. (Systèmes sylvopastoraux. Pour un environnement, une agriculture et une économie durables, 1995)
The relationship between forage yield and number of flowering stems along with their genetic variability was studied in a population of Phalaris aquatica L. composed of eighty plants collected from representative regions of Greece. The plants were transplanted and maintained in an isolation field located in Macedonia, Greece. Two trials were established in 1989, one for HS families and another for clone evaluation by using an incomplete block design. Measurements were taken at the end of June 1991 and 1992. The number of flowering stems per plant varied considerably among HS families and clones in both years. No interaction between families and years was found. The year effect was highly significant, resulting in a 58 per cent reduction in the number of stems per plant for HS families and 79 per cent for the clones in the dry year 1992 as compared to 1991. Variance among HS families was not significant, but highly significant for the clones. The genetic variance component (sigma2g) was much higher in the favourable year 1991 for both types of progenies, especially for clones. The values of the genetic coefficient of variation (GCV) for HS families and clones were very satisfactory suggesting that genetic variance is present in the population for effective selection. Positive correlation between forage yield and the number of flowering stems was found although the relationship explained only 60 per cent of the variance, indicating that selection for high forage yield with low number of stems should be effective.
Réunion du Groupe de Travail Méditerranéen du Réseau Interrégional FAO/CIHEAM de Recherche et Développement sur les Pâturages et les Cultures Fourragères, 1995/05/29-1995/06/02, Avignon (France)